2007
DOI: 10.1007/s00134-007-0606-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug sequestration during extracorporeal membrane oxygenation: results from an ex vivo experiment

Abstract: Our ex vivo study demonstrates serial losses of several drugs commonly used during ECMO therapy. Therapeutic concentrations of fentanyl, voriconazole, antimicrobials and heparin cannot be guaranteed in patients on ECMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
144
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 29 publications
6
144
1
1
Order By: Relevance
“…However, the data suggest that the ECMO circuit can substantially alter the PK of antimicrobials resulting in changes to elimination and volume of distribution [155][156][157][158][159][160][161][162][163]. In addition, the critical condition of the patients in need of ECMO and the number of days on ECMO may further impact the PK changes observed.…”
Section: Triazoles and Extracoporeal Membrane Oxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data suggest that the ECMO circuit can substantially alter the PK of antimicrobials resulting in changes to elimination and volume of distribution [155][156][157][158][159][160][161][162][163]. In addition, the critical condition of the patients in need of ECMO and the number of days on ECMO may further impact the PK changes observed.…”
Section: Triazoles and Extracoporeal Membrane Oxygenationmentioning
confidence: 99%
“…However, one ex vivo study using blood primed ECMO circuits demonstrated a dramatic decrease in voriconazole levels of 60% over 3 hours [157]. Since the circuit was not connected to a patient and the result was compared to a control specimen, drug loss was attributed to interactions between the drug and circuit [157].…”
Section: Triazoles and Extracoporeal Membrane Oxygenationmentioning
confidence: 99%
“…7 Newer data have shown no alteration in PB concentrations and a smaller impact (17.6%-31.4%) on phenytoin concentrations. 9 The extent to which the drug was lost in these studies was dependent on the duration of circuit use as well as the agent used to prime the circuit. 7,9 Each study's results vary based on the components used in the ECMO circuit.…”
Section: Introductionmentioning
confidence: 97%
“…9 The extent to which the drug was lost in these studies was dependent on the duration of circuit use as well as the agent used to prime the circuit. 7,9 Each study's results vary based on the components used in the ECMO circuit. There is also evolving technology in which different components of the ECMO circuit are being upgraded.…”
Section: Introductionmentioning
confidence: 97%
“…Generally, ECMO may cause increases in V d for certain drugs as well as the possible binding of drugs in the ECMO circuit [72]. However, the variable characteristics of ECMO technologies and settings (e.g.…”
Section: Extracorporeal Membrane Oxygenationmentioning
confidence: 99%